1991
DOI: 10.1172/jci115382
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing of proenkephalin-A by human peripheral blood monocytes and T lymphocytes.

Abstract: Human peripheral blood mononuclear cells are analyzed for preproenkephalin gene expression and peptide processing.Met-enkephalin immunoreactivity as detected with a specific antiserum is found in the cytoplasm of monocytes but not in T lymphocytes. Secretion of met-enkephalin was analyzed with an RIA that is specific for the met-enkephalin pentapeptide. Unfractionated PBMC spontaneously released 40 pg/ml met-enkephalin and this increased two-to fourfold after stimulation with PHA. Lower levels (< 100 pg/ml) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…In the present study, we did not find any correlation between the enk level and the histological changes. Previously, it has been shown that enkephalin synthesis is upregulated mainly in activated mononuclear cells [4, 24, 25]. Therefore, the lacking correlation might indicate that the production of enkephalin ceases before the infiltrating cells disappear from the skin and before the epidermal changes are normalized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we did not find any correlation between the enk level and the histological changes. Previously, it has been shown that enkephalin synthesis is upregulated mainly in activated mononuclear cells [4, 24, 25]. Therefore, the lacking correlation might indicate that the production of enkephalin ceases before the infiltrating cells disappear from the skin and before the epidermal changes are normalized.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that enkephalin-like immunoreactivity is present in CD68-positive cells infiltrating psoriatic lesions [7]. Furthermore, opioid peptides, including enkephalin have been shown in mononuclear leukocytes in inflamed tissues [1, 2, 3, 4, 7], in epidermal keratinocytes in normal skin and in various skin diseases [5, 6]. Therefore, the decrease in enk levels after local treatment with calcipotriol and mometasone furoate might result from a reduction in the number of inflammatory cells and/or in the number of proliferating epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition to their expression in neural tissues, PEA and its derived peptides are also expressed in a variety of immune cells as monocytes/macrophages, T lymphocytes, and mast cells. 12 It appears that enkephalins and more particularly, methioninenkephalin (ME) modulates immunocyte chemotaxis 13 and cytokine secretion. 14,15 For example, ME stimulates interleukin 6 (IL-6) liberation by human monocytes.…”
mentioning
confidence: 99%
“…Previous data from animal studies suggest an association with food restriction [2,3] and stress [4,5] . ppE has also been described in peripheral tissues such as the adrenal medulla, testes, kidney, heart muscle, liver, muscle and many more [6,7] , as well as in a wide variety of cells in the immune system, including T cells [8,9] , B cells [10] and monocytes [9] .…”
mentioning
confidence: 99%